2001
DOI: 10.1021/cm001203p
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of SiO2−Al2O3−CaO−P2O5−K2O−F- Glass Ceramics. 1. Needlelike versus Isometric Morphology of Apatite Crystals

Abstract: In SiO2−Al2O3−CaO−P2O5−K2O−F- glasses, either spherical or needlelike fluorapatite crystals can be formed depending on the heat-treatment schedule. If the annealing is performed at 800 °C or low heating rates are applied, isometric apatite crystallizes whereas the heat treatment at 1200 °C in conjunction with high heating rates results in apatite needles. On the basis of the combination of 31P MAS NMR spectrometry, transmission-electron microscopic imaging, and energy-dispersive X-ray spectrometry, a crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Crystallization of fluorapatite occurs within the phase separated droplets and is limited by their size, up to 500 nm, as crystal growth is hindered by the depletion in key elements of the surrounding glassy matrix. 8, 17 This leads to a microstructure of isometric fluorapatite crystals as opposed to needle-shaped crystals. 8 It was also shown that depending on their composition and connectivity, phase separated droplets (PSDs) facilitate the crystallization of fluorapatite by lowering the activation energy for FAp crystal growth and by acting as heterogeneous nucleation sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallization of fluorapatite occurs within the phase separated droplets and is limited by their size, up to 500 nm, as crystal growth is hindered by the depletion in key elements of the surrounding glassy matrix. 8, 17 This leads to a microstructure of isometric fluorapatite crystals as opposed to needle-shaped crystals. 8 It was also shown that depending on their composition and connectivity, phase separated droplets (PSDs) facilitate the crystallization of fluorapatite by lowering the activation energy for FAp crystal growth and by acting as heterogeneous nucleation sites.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies on fluorapatite glass-ceramics, showing the formation of primary Ca-P rich PSDs and secondary Al-P rich PSDs in the parent glass. 3, 17, 23 The primary PSDs later crystallize into fluorapatite during further heat treatment, while the secondary PSDs remain amorphous. It was shown that the size of the fluorapatite crystals is limited by the size of the PSDs and an isometric shape is retained at lower temperatures and for slow heating rates because diffusion rates are low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is quite unusual; in the most systems reported in the literature up to now, the opposite behavior has been reported (see e.g. [21][22][23][24]), the aspect ratio increases with increasing crystallization temperature. Anisometric crystal growth resulting in needle-like morphology has not thermodynamic reasons, such as different surface tensions in different crystallographic directions.…”
Section: Discussionmentioning
confidence: 71%
“…The growth of fluoroapatite on glass ceramics has also been reported. [42] By using an annealing temperature of 1200 C, needle-like crystals with a 15:1 aspect ratio similar to enamel crystals were observed, which could be subsequently oriented within the ceramic matrix by extrusion processing.…”
Section: Bioceramics and Bioglassesmentioning
confidence: 98%